(untitled) (Third Sector Social Economic Review, 2022)
The aim of this study is to examine the effect of organizational trust and its components on employee resilience. For this purpose, the relationship between these two concepts was discussed by using the structural equation model, and this model was applied with the participation of 390 employees in the SGK Presidency in Ankara. The scale developed by Näswall et al. (2016) to measure employee resilience was adapted to Turkish using Brislin’s (1970) method, and its validity and reliability were proven by explanatory factor analysis. The questionnaire used by Omarow in 2009 was used to measure organizational trust. In the next step, two confirmatory factor analysis models and structural equation models were created to measure the effect of organizational trust and its components on employee resilience. The fit indexes show that the models do not have fit problems, and the validity and reliability values show that the measurement models are valid and reliable, and as a result, the scales are valid and reliable. When the structural equation results are examined, it is seen that organizational trust has a positive and significant effect on employee resilience (β=.238) and trust in the organization (β=.238) and trust in management (β=.238) have a significant and positive effect on employee resilience, as well as trust in colleagues does not seem to have a significant effect on employee’s resilience.